THE IMPLEMENTATION OF LITERATURE IN EXTRACURRICULAR “STUDENT CONVERSATION CLUB” - M Yusril Rizqi Hidayat; Errend Marchella Leonic Franchsicha; Wahyu Indah Mala Rohmana (Program Studi Pendidikan Bahasa Program Pascasarjana Universitas Negeri Jakarta, 2023)
Literature is divided into two parts, namely fiction and non-fiction. Literature is not only studied within the scope of school, but there are those who study it outside the school class. One of them is extracurricular activities. The literature referred to in this extracurricular activity is fictional literature such as choirs, songs and plays. The results of previous studies state that literature such as music and poetry can improve the quality of a person's language, and not only improve language, literature can also provide space for us to express. The purpose and reason for the researcher to raise and examine this title is to provide an overview of how literature is applied in the extracurricular student conversation club and to find out what problems hinder the application of literature in the extracurricular. This research uses descriptive qualitative method. The objects of this research are coaches and extracurricular members of the 2022-2023 student conversation club with details of 1 coach and 3 members. The results of the study stated that the students' conversation club extracurricular activities had a good impact on improving students' language skills, especially in English.